2014
DOI: 10.1063/1.4887629
|View full text |Cite
|
Sign up to set email alerts
|

Free convection flow in an inclined plate with variable thermal conductivity by scaling group transformations

Abstract: Abstract. The Lie group analysis of natural convection flow over an inclined semi-infinite plate with variable thermal conductivity is studied. The fluid thermal conductivity is assumed to vary as a linear function of temperature. A scaling group of transformation is applied to the governing partial differential equations and then used to reduce them to a system of ordinary differential equations. Numerical solutions of the ordinary differential equations are also obtained. From the numerical results it is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…From the velocity solution v(y, t) computed in Eq. (33), which can easily satisfies the imposed initial / boundary conditions.…”
Section: Solution Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…From the velocity solution v(y, t) computed in Eq. (33), which can easily satisfies the imposed initial / boundary conditions.…”
Section: Solution Of the Problemmentioning
confidence: 99%
“…It is conceived that velocity, energy and concentration are functions of y and t only. The following principal equations for Oldroyd-B fluid under Boussinesq's approximation, for velocity field, concentration distribution and energy transfer are obtained as 33,34 : Also equations for heat and mass are taken as: with connected initial conditions together with boundary conditions are given below: where v(y, t) , C(y, t) and T(y, t) represents the fluid velocity, concentration andenegy distribution. Where the parameters β T , D C , β C , R C , 1 , c p , g, σ , ν, q r , ρ, k, and 2 are thermal expansion coefficient, mass diffusivity, concentration expansion coefficient, chemical reaction, relaxation time, specific heat at constant pressure, gravitational acceleration, electrical conductivity, kinematic viscosity, radiative heat flux, fluid density, thermal (1) www.nature.com/scientificreports/ conductivity and retardation time.…”
mentioning
confidence: 99%
“…The important impact of the chemical reaction and the convective surface boundary condition on the MHD magnetic heat and mass transmission upon a vertical sheet are explored by Gangadhar (2013) with the Soret and Dufour influences. Bhuvaneswari and Sivasankaran (2014) analyzed the effect of the variable thermal conductivity on the free convective heat and mass transmission movement upon an inclined semi-infinite sheet. The impacts of the chemical reaction and the radiative on a visco-elastic MHD free convective movement on a vertical permeable sheet over a perforated media are presented by Choudhury and Kumar Das (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Soret and Dufour effects on similarity solution of hydro magnetic heat and mass transfer over a vertical plate with a convective surface boundary condition and chemical reaction are studied by Gangadhar (2013). Lie group analysis of natural convection over an inclined semi-infinite plate with variable thermal conductivity is investigated by Bhuvaneswari and Sivasankaran (2014). They observed that the velocity and temperature for all angles increase when the thermal conductivity parameter increases.…”
Section: Introductionmentioning
confidence: 99%